Warriache communities: representations of urbanity in recent Mapuche writing (Anclajes, 2026)
The most recent Mapuche literature represents new forms of community that problematize forced displacement and reterritorialization in urban peripheries. Once the lof as a form of ancestral community has been disarticulated the Mapuche who reterritorialize in the cities form other kinds of groupings, where subjectivities are brought together not exclusively by their common ethnicity but through a shared history of ‘otrification’. This article focuses on the volume of stories Piñen, by Daniela Catrileo, and lines of dialogue are drawn towards a corpus of texts and paratexts marked by the intersection of urbanity and the Mapuche origin of those who produce them. The aim is to analyze what kind of ‘we’ is configured in these writings, based on the encounter of a group of subjectivities displaced from Chilean national officialdom.
Keywords: Daniela Catrileo; Mapuche Literature; Literary Criticism; 21st Century; Chile